Tertiary molluscs of the Scotian Shelf, Atlantic Canada - Cole, Fiona; Thomas, Francis (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1996)
Cuttings from the Cenozoic section of LASMO/NSRL Cohasset Producer CPl P-51, a production well on the Scotian Shelf, offshore Atlantic Canada, contain relatively large numbers of small molluscs and other microin vertebrates. The stratigraphic distributions of these taxa have been compared with the previously established foraminiferal zonation for this site. Over 50 species of these fossils arc recognized, and many represent extant forms now found in much warmer conditions than presently exist on the Scotian Shelf. Occurrences of most of these warm-water forms are concentrated in the upper portion of the Lower Eocene and lower Middle Eocene, in the lower part of the Oligocene section and, to a lesser extent, in the Lower Miocene, supporting claims for climatic warming trends during these intervals in the foraminiferal literature. There is some suggestion that at least part of the molluscan assemblage is allochthonous, having been transported into deeper waters from its ncarshore origin. If true, this does not affect paleoclimatic interpretations. If the molluscs arc in place, fluctuating numbers of these taxa with respect to foraminiferal numbers may suggest differences in the parameters affecting the productivity of the two groups. The restricted stratigraphic ranges of some of these forms may prove useful in correlations with other Atlantic Canada sites where foraminiferal assemblages are impoverished. In one of the Cohasset species, the serpulid worm Paliurus, the known stratigraphic range appears to be extended from the Eocene up to the Oligocene. A second species, "Coleolus", present in Paleocene to Oligocene horizons, appears to be a homeomorph of a little-known Palaeozoic form. The absent or very condensed Upper Eocene section of CPl P-51 may be related to increased deep-ocean circulation in the Early Oligocene, as suggested in some foraminiferal literature.